A stepwise composite echocardiographic score predicts severe pulmonary hypertension in patients with interstitial lung disease. Issue 2 (4th May 2018) - Bax, Simon; Bredy, Charlene; Kempny, Aleksander; Dimopoulos, Konstantinos; Devaraj, Anand; Walsh, Simon; Jacob, Joseph; Nair, Arjun; Kokosi, Maria; Keir, Gregory; Kouranos, Vasileios; George, Peter M.; et al.
European Respiratory Society (ERS) guidelines recommend the assessment of patients with interstitial lung disease (ILD) and severe pulmonary hypertension (PH), as defined by a mean pulmonary artery pressure (mPAP) ≥35 mmHg at right heart catheterisation (RHC). We developed and validated a stepwise echocardiographic score to detect severe PH using the tricuspid regurgitant velocity and right atrial pressure (right ventricular systolic pressure (RVSP)) and additional echocardiographic signs. Consecutive ILD patients with suspected PH underwent RHC between 2005 and 2015. Receiver operating curve analysis tested the ability of components of the score to predict mPAP ≥35 mmHg, and a score devised using a stepwise approach. The score was tested in a contemporaneous validation cohort. The score used "additional PH signs" where RVSP was unavailable, using a bootstrapping technique. Within the derivation cohort (n=210), a score ≥7 predicted severe PH with 89% sensitivity, 71% specificity, positive predictive value 68% and negative predictive value 90%, with similar performance in the validation cohort (n=61) (area under the curve (AUC) 84.8% versus 83.1%, p=0.8). Although RVSP could be estimated in 92% of studies, reducing this to 60% maintained a fair accuracy (AUC 74.4%). This simple stepwise echocardiographic PH score can predict severe PH in patients with ILD. A stepwise echocardiographic score to predict severe group 3 pulmonary hypertension http://ow.ly/9cIC30iGSMj